Entropic information theory applied to uncertainty in financial markets - Dionísio, Andreia (2012)
One of the most popular concepts used to measure the risk and the uncertainty is the variance and/or the standard-deviation. In this paper we explore the potentialities of the entropy as a measure of uncertainty in financial markets, and simultaneously verify if this measure take into account some basic assumptions of the portfolio management theory, namely the effect of diversification.